2016
DOI: 10.1002/slct.201600369
|View full text |Cite
|
Sign up to set email alerts
|

Redox Partner Interaction Sites in Cytochrome P450 Monooxygenases:In SilicoAnalysis and Experimental Validation

Abstract: The native redox partners of many novel cytochrome P450 monooxygenases (CYPs) are unknown. Therefore, they are combined with non‐native redox partners to obtain catalytically active systems. Understanding the CYP‐redox partner interactions is the basis of successful protein engineering. Six redox partner interaction sites (RPISs) were identified by systematic literature, sequence, and structure analyses. All six RPISs are proposed to contribute to class II CYP‐redox partner interaction interface, whereas four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
(130 reference statements)
0
6
0
Order By: Relevance
“…has been fused to the cytochrome P450 reductase (CPR) domain of CYP102A1 (BM3), the PFOR domain of CYP116B3 [13] and CYP116B2 [10]. This is however no trivial task, as not only do the linker region's sequence and length significantly influence the activity and coupling efficiency [10] but given that these reductase partners are not the CYPs' natural redox partners, interdomain contacts also have to be optimized [14]. Although higher coupling efficiencies have been observed with artificial fusion systems such as CYP153A35 fused to the CPR of P450BM3, CYP153A35 displayed higher productivities in whole cells when used as a three-component system in combination with putidaredoxin (CamB) and putidaredoxin reductase (CamA) [15].…”
Section: Introductionmentioning
confidence: 99%
“…has been fused to the cytochrome P450 reductase (CPR) domain of CYP102A1 (BM3), the PFOR domain of CYP116B3 [13] and CYP116B2 [10]. This is however no trivial task, as not only do the linker region's sequence and length significantly influence the activity and coupling efficiency [10] but given that these reductase partners are not the CYPs' natural redox partners, interdomain contacts also have to be optimized [14]. Although higher coupling efficiencies have been observed with artificial fusion systems such as CYP153A35 fused to the CPR of P450BM3, CYP153A35 displayed higher productivities in whole cells when used as a three-component system in combination with putidaredoxin (CamB) and putidaredoxin reductase (CamA) [15].…”
Section: Introductionmentioning
confidence: 99%
“…7 The proximal face of a P450 is also the site where interactions with redox partner proteins occur, with these processes largely appearing to be driven by electrostatic interactions. 8 The active site of P450s comprises regions that surround the distal face of the heme moiety, and include the so-called BC loop region between the B-and C-helices, the C-terminal region of the F-helix, the N-terminal portion of the G-helix, the centre of the I-helix, the b-strand following the K-helix and the C-terminal loop that impinges of the P450 active site (such regions are also referred to as substrate recognition sites, SRSs 1-6). 9 Variability within these regions leads to the ability of P450s to accept a wide range of different substrates (even those that are protein bound), whilst the retention of the general structure surrounding the active site heme group and axial cysteine ligand support the remarkable consistency of the P450 catalytic mechanism.…”
Section: 3mentioning
confidence: 99%
“…Computational analysis indicated that electron transfer from FMN-toheme in the conformation observed in the crystal structure would take ~50 years to complete for an extended ~50 σ-bond route (through amino acids and their peptide bonds) from FMN-to-heme. This is unlikely to be an efficient electron tunnelling pathway, and an alternative route of ~18 Å between conjugated edges of the FMN cofactor and the heme prosthetic group was calculated to have an electron transfer rate constant of ~12 s -1 (1,16,35). Despite this, modelling of the interactions between the BM3 heme domain and the FMN domain identifies larger regions of interest from the 1BVY structure.…”
Section: Discussionmentioning
confidence: 99%